Komunikasi Visual Kajang Dalam Upacara Ngaben di Bali - Swandi, I Wayan; Nuriarta, I Wayan (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
Kajang is one of the essential elements in Balinese death rites. Kajang, as a symbol, has visual communication because it is a representation of the meanings of life. This research aims to classify the Kajang's appearance and interpret the Kajang's rerajahan from a visual communication perspective as the ceremony's spirit. The benefit of this research is that it can be used as a reference in classifying the visual appearance of awnings and is useful for understanding the meaning of awnings, so that awnings can be widely recognized by the Balinese people. The research method used is a critical qualitative method with the point of view of cultural studies.The results show that in the Hindu tradition, especially in Bali, Kajang is written in the Modre script and the Swalalita script and then placed on the curvature of the person to be incised. The types of Kajang in the composition of Ulaka Warih Ida Bhatara Dalem Benculuk Tegeh Kori, namely; (1) Kajang Klasa Walaka, (2) Kajang Pemijilan Walaka, (3) Kajang Kawitan Walaka, (4) Kajang Recedana Walaka, and (5) Kajang Sari/ Siwa Walaka. Kajang in Balinese Hindu tradition is a symbol (pengawak) of the spiritual and physical bodies of people who have died. In visual communication, Kajang is an illustration that explains a narrative of life. Religiously, the Kajang is a religious symbol with the meanings of human life.